Maternal body mass index affects the dose of enoxaparin required to achieve effective thromboprophylaxis during pregnancy. (16th November 2010) - Denison, FC; Walker, MC; Horn, L; Stock, SJ; Norman, JE
Abstract : Background: Maternal obesity is an important risk factor for venous thromboembolism and it is recommended that women with a body mass index (BMI) >40 kg/m 2 should be considered for postpartum thromboprophylaxis with low molecular weight heparin (LMWH). However, there is little data available regarding the effect of maternal BMI on LWMH efficacy, or the optimal dose required in obese women. The aim of this study was to determine if the dose of the LMWH Enoxaparin required to achieve effective thromboprophylaxis is affected by maternal BMI. Methods: The authors performed a cohort study of women who received antenatal thromboprophylaxis with Enoxaparin between January 2005 to December 2008 (n=78), Anti-Xa levels were monitored, with a value between 0.2 and 0.4 U/ml defined as effective prophylaxis. Doses required to achieve these levels were compared in obese (BMI ≥30 kg/m 2 ) and non-obese women (BMI <30 kg/m 2 ). Results: The modal dose (range) of Enoxaparin administered was 40 mg (20–60 mg). Overall 44.9% (35/78) of women required their dose of Enoxaparin to be increased and 79.4% (62/78) had effective thromboprophylaxis by the end of pregnancy. More obese women required their dose to be increased than non-obese women (p=0.03) and at term the dose of Enoxaparin was higher in obese women than non-obese women (modal dose 50 vs 40 mg). Conclusion: Obese women require a higher dose of Enoxaparin to achieve effective thromboprophylaxis compared to women of normal weight. This has implications for clinical practice and suggests that monitoring of anti-Xa levels may be required for obese women on LMWH thromboprophylaxis during pregnancy and post partum.